The Palgrave Handbook of Critical Menstruation Studies
L, 1037 p. 48 illus., 33 illus. in color.
Keywords: This open access handbook, the first of its kind, provides a comprehensive and carefully curated multidisciplinary genre-spanning view of the state of the field of Critical Menstruation Studies, opening up new directions in research and advocacy. It is animated by the central question: ‘“what new lines of inquiry are possible when we center our attention on menstrual health and politics across the life course?” The chapters—diverse in content, form and perspective—establish Critical Menstruation Studies as a potent lens that reveals, complicates and unpacks inequalities across biological, social, cultural and historical dimensions. This handbook is an unmatched resource for researchers, policy makers, practitioners, and activists new to and already familiar with the field as it rapidly develops and expands.